2016
DOI: 10.1088/1748-6041/11/1/015017
|View full text |Cite
|
Sign up to set email alerts
|

Creating tissues from textiles: scalable nonwoven manufacturing techniques for fabrication of tissue engineering scaffolds

Abstract: Electrospun nonwovens have been used extensively for tissue engineering applications due to their inherent similarities with respect to fibre size and morphology to that of native extracellular matrix (ECM). However, fabrication of large scaffold constructs is time consuming, may require harsh organic solvents, and often results in mechanical properties inferior to the tissue being treated. In order to translate nonwoven based tissue engineering scaffold strategies to clinical use, a high throughput, repeatabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Non‐woven scaffolds have been extensively investigated and used in tissue engineering applications as they are inherently analogous to native extracellular matrix (ECM) in terms of fiber size and morphology. [ 172‐174 ] However, there are a number of limitations of non‐woven PGA scaffolds such as difficulties in controlling mechanical properties and the porous structure parameters including pore connectivity, pore size distribution, and pore spatial distribution. [ 175 ] On the contrary, the woven structures are proposed to have high strength and dimensional stability and low permeability to blood, and are also less liable to kinking.…”
Section: Potential Future Work and Their Associated Challengesmentioning
confidence: 99%
“…Non‐woven scaffolds have been extensively investigated and used in tissue engineering applications as they are inherently analogous to native extracellular matrix (ECM) in terms of fiber size and morphology. [ 172‐174 ] However, there are a number of limitations of non‐woven PGA scaffolds such as difficulties in controlling mechanical properties and the porous structure parameters including pore connectivity, pore size distribution, and pore spatial distribution. [ 175 ] On the contrary, the woven structures are proposed to have high strength and dimensional stability and low permeability to blood, and are also less liable to kinking.…”
Section: Potential Future Work and Their Associated Challengesmentioning
confidence: 99%
“…There have been limited previous studies to evaluate meltblown fabrics for tissue engineering purposes, but promising work has assessed this technique for vascular tissue engineering. 17 Additional recent studies confirmed that meltblown and other nonwoven poly(lactic acid) (PLA) fabrics supported attachment, 18 proliferation, and differentiation of human adipose-derived stem cells (hASCs) toward osteogenic and adipogenic lineages 14,19 to a similar extent as single-layer electrospun PLA scaffolds. To the best of our knowledge, meltblown scaffolds have not been evaluated for tendon tissue engineering.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, these previous studies used induction media to induce lineage specific differentiation. 14,17,19 In contrast, we have not previously used tissue-specific induction media or exogenous growth factors in our rotator cuff tendon tissue engineering studies, 4,11 since this approach could confer several regulatory advantages and could be beneficial if the expression of multiple tissue lineages is desired within the same scaffold. In the current study, our overall aim was to evaluate meltblown fabrics for use in rotator cuff tendon tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In tissue engineering, there is an increasing need for scaffold fabrication methods with higher throughput, lower cost, and improved reproducibility . Efforts have been made to investigate the potential of using currently available industrial‐scale polymer processing technologies to produce tissue engineering scaffolds …”
Section: Introductionmentioning
confidence: 99%
“…The randomly arranged microfibers that are generated have gained interest for industrial applications, in particular for use in filtration or barrier materials . Our laboratory has also recently shown that microfibers obtained from the SpunBlown® process mimic the fibrillar structure of native extracellular matrix (ECM), allowing for improved cellular attachment and proliferation . Compared to the conventional tissue engineering scaffold fabrication methods, such as electrospinning, SpunBlown® provides an alternative approach to produce ultra‐fine fibrous materials with higher throughput, lower cost, and enhanced reproducibility …”
Section: Introductionmentioning
confidence: 99%